Community Network Forum : Addressing Mental Health Issues : An Emerging Challenge for Community Resources - Réseau de l’est de l’île pour les services en anglais (REISA) (2011)
The forum will address the challenges that community resources face as an increasing number of those seeking their services show signs of psychological distress and poor mental health. What is the impact of this emerging clientele on community programs? Where do community resources refer persons in difficulty? How should programs be adapted to address the new challenge? What are the policy and program responses of government and the public health and social services?

East-Island Network Newsletter : Reisaction - Réseau de l’est de l’île pour les services en anglais (REISA) (2011)
Number of pages: 4

East-Island Network Newsletter : Reisaction - Réseau de l’est de l’île pour les services en anglais (REISA) (2011)
Number of pages: 6